THE EFFECT OF USING DIRECT FEEDBACK ACCORDING TO DIFFERENT LEARNING STYLES (AUDITORY-KINESTHETIC) ON ACQUIRING THE TECHNICAL PERFORMANCE OF THE LONG JUMP - Assoc. Prof. Dr. Murad Ahmed Yass; Assoc. Prof. Dr. Ali Abdul Aleem Mohammed Saber; Teacher. Omar Awid Saleh (Proximus Journal Publishing, 2025)
The problem of the research lies in answering the following question: Does using direct feedback according to two learning styles (auditory feedback) or (kinesthetic feedback) lead to better results in acquiring the technical performance of the long jump among students of the College of Physical Education and Sports Sciences, University of Kirkuk? The aim of the research is to examine the effect of using direct feedback according to two learning styles (auditory and kinesthetic) on acquiring the technical performance of the long jump among first-year students at the College of Physical Education and Sports Sciences. The researchers used the experimental method due to its suitability for the nature of the research. The researchers concluded that there is a positive effect of the educational programs implemented by the two experimental groups that used direct feedback according to the learning styles (auditory and kinesthetic) on acquiring the technical performance of the long jump among first-year students at the College of Physical Education and Sports Sciences, University of Kirkuk, in addition to the positive results of the control group. They recommended the use of the two educational programs developed by the researchers, which utilized (direct feedback according to auditory and kinesthetic learning styles) in acquiring the technical performance of the long jump for first-year students in the College of Physical Education and Sports Sciences
Keywords: direct feedback; auditory learning style